Implementasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) dalam Meningkatkan Efisiensi Pelayanan - Didit Setiawan; Achmad Fauzan Rachman (Lembaga Pengembangan Kinerja Dosen, 2026)
The implementation of Hospital Management Information Systems (HMIS) has become a strategic imperative to enhance operational efficiency amidst the ongoing global digital health transformation era. This study aims to analyze the determinants of successful HMIS implementation and its impact on service efficiency and patient outcome quality. Employing a narrative review approach with thematic synthesis of literature from PubMed, Scopus, and ScienceDirect databases between 2016-2026, the study evaluates the relationship between technology investment and organizational performance. The synthesis results indicate that while HMIS significantly reduces administrative burdens and medication errors, a